Rhetorical Structure on Research Article Abstracts in Informatics and Computer Science Journals - Nurhayati S; fadilah fadilah; Fiza Asri Fauziah Habibah (Universitas Nasional, 2022)
ABSTRACTIn order to attain coherence, research abstracts must contain a number of crucial steps, although these steps do not always follow the same sequence. Contexts tend to dictate different writing styles. This study looked at how the rhetorical structure or move structures were used, distributed, and arranged in 30 abstracts as incorporating of two Computer Science & Engineering, and Information Systems journals in Indonesia. Each move was classified and categorized using the five-move analysis paradigm developed by Hyland. Findings from the analysis showed that there were 12 organizational move pattern appears. Some had all the five moves, some had four moves and others only three. There were 15 abstracts that contained all the five moves identified with 9 abstracts following the framework M1-M2-M3-M4-M5, while the other 6 are random. 13 abstracts contained 4 moves with 10 following the M1-M2-M3-M4 pattern, while the other 3 are random. Another 2 abstracts only contained three moves with M1-M2-M3 and M1-M2-in pattern. In conclusion, this present study showed that the 50% of RA abstracts of the two journals have fulfilled the Hyland’s five model. Furthermore, in order to assist the student researchers in creating well-written abstracts, it would be good to provide explicit training and experiential learning through a genre-based approach.